2017
DOI: 10.1007/s12039-017-1243-0
|View full text |Cite
|
Sign up to set email alerts
|

A model with charges and polarizability for CS2 in an ionic liquid

Abstract: The environment of a solute molecule in an ionic liquid is likely to have large fluctuating electrostatic fields, and so the electrostatic properties of such a solute including its charge distribution and its polarizability may make a difference to both its static and dynamic properties. We have developed a new model for the static electrostatic distribution in the CS 2 molecule with 7 charged sites and anisotropic polarizability on the carbon site and isotropic polarizability on the sulfurs. We have investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…For instance, Stasyuk and coworkers [104], as well as several others [195], have recently proposed new models for evaluating charges that could be utilized for arriving at a fundamental understanding of some chemical systems, including endohedral fullerenes. Evidently, atomic charge is certainly a valuable property [196] that will continue to play a crucial role in the understanding systems in diverse areas of science.…”
Section: Is the Concept Of Atomic Charge Meaningful?mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Stasyuk and coworkers [104], as well as several others [195], have recently proposed new models for evaluating charges that could be utilized for arriving at a fundamental understanding of some chemical systems, including endohedral fullerenes. Evidently, atomic charge is certainly a valuable property [196] that will continue to play a crucial role in the understanding systems in diverse areas of science.…”
Section: Is the Concept Of Atomic Charge Meaningful?mentioning
confidence: 99%
“…We note further that the sulfur quadrupole moment in CS 2 is positive and, and, there is negative π-electron density around the S atom but a positive σ-hole along the axis. The carbon quadrupole moment is negative, reflecting a reduced π-electron density around the C atom [196]. Because of this nature of the molecule, Singh et al [281] found that the molecule displays versatile coordination modes, and has ability to feature crossed, parallel-stacked, T-shaped, and L-shaped geometries in its clusters.…”
Section: Examples Of Some Crystalmentioning
confidence: 99%
“…Figure 3 shows the electrostatic field around a CS 2 molecule (left) and the difference between this and two point charge models (centre and right). The centre figure shows the result from the best model with charges on the three sites, while the right hand figure shows the improvement obtained by adding additional charges on either side of the S sites making a 7-site model [21]. However this is a case where the polarisability may be important and site polarisabilities were calculated with Misquitta and Stone's CamCASP program [22].…”
Section: Csmentioning
confidence: 99%
“…Due to symmetry the average electric field must be zero at each site, although there are fluctuations in its value. In the [dmim][NTf 2 ] and [bmim][NTF 2 ] solutions we found that the root mean square (rms) value of the field components at each site was 0.13pm0.02V/ Å perpendicular to the axis and 0.24±0.02V/ Å along the axis [21]. The fields tend to be largest along the molecular axes.…”
Section: Csmentioning
confidence: 99%
“…Aim of this work was to further optimize the force field of Pádua et al to better represent dynamical properties like selfdiffusion coefficients, reorientational correlation times, and viscosities. As shown in their original work from 2007 as well as in further works published by different groups, the KPL force field has been proven to yield reliable results for dynamical properties, but also thermodynamical properties, such as the free energies of solvation for light gases in ionic liquids [17,18], and is still used frequently to this date [19][20][21].…”
Section: Introductionmentioning
confidence: 99%